Inherently Safer Design and Process-Safety Management - Kletz, Trevor A.; Amyotte, Paul (Process Plants, 2010)
Given the above quote by Peter Drucker, perhaps leadership should be substituted for management in the title of this chapter. Without capable and courageous leadership, safety management efforts are effectively wasted. The industry term is, however, process-safety management, and that is the subject of this chapter.